2009
DOI: 10.1254/jphs.08257sc
|View full text |Cite
|
Sign up to set email alerts
|

A Receptor-Independent Effect of Estrone Sulfate on the hERG Channel

Abstract: Abstract. We recently reported that physiological concentrations of 17β-estradiol partially down-regulate cardiac rapidly-activating delayed rectifier K + currents (hERG currents) independently of estrogen-receptor signaling. To determine if other estrogens have the same effect as that of 17β-estradiol, we investigated receptor-independent effects of estrone, estrone 3-sulfate, and estriol on hERG currents in patch-clamped estrogen-negative HEK293 cells. Only estrone 3-sulfate partially suppressed hERG current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…This is consistent with the less clear impact of circulating estrogen on fluctuation of female baseline QT C intervals during the menstrual cycle than that of progesterone (21,28,30). Very recently, we found that estrone 3-sulfate at physiological concentrations in both women and men at any ages can suppress hERG currents with the maximal extent of effectiveness (48).…”
Section: Estrogensupporting
confidence: 88%
“…This is consistent with the less clear impact of circulating estrogen on fluctuation of female baseline QT C intervals during the menstrual cycle than that of progesterone (21,28,30). Very recently, we found that estrone 3-sulfate at physiological concentrations in both women and men at any ages can suppress hERG currents with the maximal extent of effectiveness (48).…”
Section: Estrogensupporting
confidence: 88%
“…[29][30][31][32][33][34] Testosterone decreases calcium channel current and increases potassium channel current and may shorten the QT interval through these mechanisms. For example, in the guinea pig model, administration of 100 nM of testosterone caused dose-dependent shortening of the action potential duration through suppression of I Ca,L channels and enhancement of I Ks channels in ventricular myocytes.…”
Section: Mechanisms and Pathophysiology Of Sex Hormonal Effects On Qtmentioning
confidence: 99%
“…Does it represent an endpoint in metabolism of E 2 , to an inactive product, or does it serve as a source for later retrieval of an active estrogen by means of an estrogen sulfatase? A recent report provides an alternative answer based on a demonstration of a receptor-independent effect of physiological levels of E 1 S (Kakusaka et al 2009). Lastly, the presence of other forms of conjugation, accounting for about one-third of conjugates, suggests further activity on the part of the embryo proper in regulating its exposure to biologically active estrogens.…”
Section: Discussionmentioning
confidence: 99%